Perfluorinated carboxylic acids discharged from the Yodo River Basin, Japan. (November 2015) - Niisoe, Tamon; Senevirathna, S.T.M.L.D.; Harada, Kouji H.; Fujii, Yukiko; Hitomi, Toshiaki; Kobayashi, Hatasu; Yan, Junxia; Zhao, Can; Oshima, Masayo; Koizumi, Akio
Highlights: We investigated PFCAs with 7–14 carbons in the Yodo River system, Japan, in 2013. The median total PFCAs was 11.2 ng L − 1 (range 1.0–89.7). The dominant component was PFOA, followed by PFHpA and PFNA. The estimated flux of discharged total PFCAs was 237.0 g d − 1 . Abstract: We investigated perfluorinated carboxylic acids (PFCAs) with 7–14 carbon atoms (C7–C14) in the Yodo River system in 2013. C7–C11 were detected at most sampling sites. The range and median of total PFCAs (ΣPFCAs) concentrations were 1.0–89.7 and 11.2 ng L −1, respectively. The dominant component was C8 (average for all samples = 53.3 ± 8.8%), followed by C7 (19.2 ± 6.7%) and C9 (17.6 ± 7.1%). The levels of C8 were confirmed to decrease greatly over the last 10 years. We assessed the fluxes in C7–C11 discharged from the basin based on the concentrations in river water and river flow rate. The flux of discharged ΣPFCAs was 237.0 g d −1 at the most downriver point of the assessment areas. Considering the variability in flow rate due to precipitation, the annual ΣPFCAs flux was estimated to be 86.5–173.4 kg y −1 . Identification and quantification of PFCAs sources is difficult because the strength of the sources changes with time, and available information is quite limited. Further monitoring and investigation are necessary to understand sources of PFCAs, as well as their potential for human exposure.